Lateral Torsional Buckling of Steel Beams under Transverse Impact Loading - Wenna Zhang; Feng Liu; Feng Xi (Shock and Vibration)
This study employs experiments and numerical simulation to analyze the dynamic response of steel beams under huge-mass impact. Results show that lateral torsional buckling (LTB) occurs for a narrow rectangular cross-section steel beam under transverse impact. The experiments were simulated using LS-DYNA. The numerical simulation is in good agreement with experimental results, thus indicating that the LTB phenomenon is the real tendency of steel beams under impact. Meanwhile, the study shows that LS-DYNA can readily predict the LTB of steel beams. A numerical simulation on the dynamic response of H-shaped cross-section steel beams under huge-mass impact is conducted to determine the LTB behavior. The phenomenon of dynamic LTB is illustrated by displacement, strain, and deformation of H-shaped steel beams. Thereafter, a parametric study is conducted to investigate the effects of initial impact velocity and momentum on LTB. The LTB of H-shaped cross-section steel beams under transverse impact is primarily dependent on the level of impact kinetic energy, whereas impact momentum has a minor effect on LTB mode.